Aqua drugs and chemicals used in aquaculture of Zakigonj upazilla, Sylhet - Chowdhury, Afnan Alam; Uddin, Md Shahab; Vaumik, Suvashis; Asif, Abdulla Al (Asian Journal of Medical and Biological Research, 2015)
In order to investigate present status of aqua chemicals and drugs used in various aquaculture activities in Zakigonj upazilla, Sylhet. A survey was conducted, with carp polyculture, tilapia and catfish farmers, aqua-medicine sellers, representatives of pharmaceuticals companies, from July 2014 to November 2014. Each group consisted of 25 respondents. According to the survey the most common dose of lime used by the farmers during pond preparation (62.67%) and culture period (53%) is 0.5-1 kg/40m2. Urea and TSP used by the farmers mostly during culture period with most common dose of 100-150g/40m2(37.3%) and 50-100 g/40m2 (68%) respectively. Various categories of aqua drugs and chemicals were identified that were used by fish farmers for different purposes such as water quality management, disinfectants, improve dissolve oxygen level, disease treatment, antibiotics and growth promoter. Many pharmaceutical companies were found to provide these aqua drugs and chemicals with different trade names to fulfill the farmers demand. For pond and water quality management lime, urea and TSP are mostly used. Bleaching powder, Timsen, EDTA, Polgard, Virex, Aquakleen, Germnill, Pond safe were widely used as disinfectant. Health management and disease treatment were the major activities where farmers were seen to use a lot of chemicals. A range of chemicals including antibiotics were found available in market and being used in the aquaculture sector. Commonly found traditional chemicals in heath management included Potassium permanganate, Lime, Salt, Virex, Timsen, Aquakleen, Germnil, Pond Safe, Deletrix, Spa, Albez, Ablez were used regularly for disease treatment. Mostly used antibiotics are Renamycin, Oxysentin 20% Chlorsteclin Oxy-D Vet, Aquamycin, Orgamycin 15 %, Orgacycline-15% etc. Major active ingredients of these antibiotics were oxytetracycline, chlorotetracycline, amoxicillin, doxycycline etc. There are approximately fifty two pharmaceutical companies have been recorded to market around 300 products. Most of the products have been marketed from different countries like USA, Thailand, Malaysia, Belgium and China etc. The study also indicated some problems associated with the use of such chemicals due to lack of knowledge of farmers about the use of chemicals, appropriate dose, method of application and their indiscriminate use of chemicals. The study also highlighted the names and approximate price of aquaculture chemicals available with the chemicals sellers in Zakigonj, Sylhet. Asian J. Med. Biol. Res. June 2015, 1(2): 336-349